Hysteresis effect on earthquake risk assessment of moment resisting frame structures - Huang, Zhenhua; Cai, Liping; Pandey, Yashica; Tao, Yong; Telone, William (Engineering structures, 2021)
•Effects of hysteresis behaviors on earthquake fragility curves of MRF structures.•A group of earthquake fragility curves for designs of NEHRP MRF structures.•A group of hysteresis behavior reduction factors for MRF building design. It is essential to estimate the earthquake-induced risks of buildings. However, most popularly used earthquake fragility curves of moment-resisting frame buildings, such as the Hazards United States (HAZUS) Earthquake model, did not consider the effects of different hysteresis behaviors. This study aims at analyzing the hysteresis effects on the earthquake fragility curves of the Moment Resisting Frame Structures (MRFs) to extend applications of these curves. The SAC projected 3-story and 9-story MRF buildings were used in this study as examples. Hysteresis behaviors of the beam-column joint were used to describe the different behaviors of different types of National Earthquake Hazards Reduction Program (NEHRP) MRF structures. ELEMENT 10 in the DRAIN-2DX program was adopted to model these hysteresis behaviors of MRF joints. The fragility curves of 3-story and 9-story steel and RC MRF buildings with different hysteresis behavior models were successfully constructed using the cumulative lognormal distribution function. Based on these fragility curves, the seismic damage safeties of all MRF buildings with different hysteresis models and at different damage limit states were analyzed and compared. The results suggested that designers could utilize some reduction factors to conservatively design the structures when using the existing earthquake fragility analysis procedure for MRF structures, such as HAZUS, given the hysteresis behaviors of NEHRP MRF types. The earthquake fragility curves presented in this study could be directly adopted for the analysis of hysteresis behaviors of NEHRP MRF structures.